Cavitation on the tip of a fibre optic : from a single bubble to a bubble cloud - Milad Mohammadzadeh (2018)
Minimally-invasive surgeries rely heavily on the use of fibre optics to steer through small incisions on the body and deliver laser pulses to remove unwanted tissue. Laser-induced heating at the fibre tip leads to vaporisation and formation of cavitation bubbles. These bubbles play two crucial roles in laser surgery: they act as transmission channels that connect the fibre tip to the ablation target and generate mechanical effects and motion in their surroundings. This thesis focuses on the dynamics of laser-generated bubbles, especially on the tip fibre optics.